Power series with radius of convergence zero - overconvergence, elongations, summability - W. Luh; A. Stepanyan (Հայաստանի ԳԱԱ)
We deal with overconvergence phenomena of power series with radius of convergence zero. Among others it is shown that the partial sums of such series can be elongated to become Cesaro summable on a set S ⊂ {z : |z| > 0} if and only if the considered power series is overconvergent.
Keywords: Science; Mathematics